Retrospective Evaluation of Deep Transcranial Magnetic Stimulation as Add-On Treatment for Parkinson’s Disease - Torres, Francisco; Villalon, Esteban; Poblete, Patricio; Moraga-Amaro, Rodrigo; Linsambarth, Sergio; Riquelme, Raúl; Zangen, Abraham; Stehberg, Jimmy (Frontiers in Neurology, 2015)
Objective To evaluate the safety and assess the different symptom improvements found after a combined low frequency primary motor cortex and high frequency prefrontal cortex stimulation using the deep TMS (dTMS) H-coil, as an add-on treatment for Parkinson´s disease (PD). Methods: 45 PD patients underwent 14 dTMS sessions; each consisting of 1Hz stimulation of the primary motor cortex for 15 min, followed by 10Hz stimulation of the prefrontal cortex for 15 min. Clinical assessments were performed, at the START, MIDDLE, and END of therapy as well as at FOLLOW-UP after 30 days, using MDS-UPDRS, TINETTI, UP&GO, SCOPA, HDRS21, BDI and self-applied daily motor assessment scales. Results: Treatment was well tolerated, without serious adverse effects. Treatment induced significant PD symptom improvements at END and at FOLLOW-UP, in all subscales of the UPDRS, gait speed, depressive symptoms, balance, autonomic symptoms and a 73% increase in daily ON time. Conclusions: In the cohort of PD patients treated, dTMS was well tolerated with only minor adverse effects. The dTMS induced significant improvements in motor, postural, and motivational symptoms of PD patients and may potentiate concurrent levodopa treatment. Significance: The present study demonstrates that dTMS may have a much wider spectrum of beneficial effects than previously reported for TMS, including enhancement of levodopa effects, suggesting that future clinical trials with dTMS should include a broader range of symptom measurements.